Student Motivation in Online English Learning - Andhina Ika Sunardi (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This study aims to discover and describe the condition of the motivational object experienced by students in online English learning during the COVID-19 pandemic. This research was conducted in Yogyakarta in the even learning year 2020/2021. Sampling was done using a purposive sampling technique, and four classes were obtained, each of which there was 32 students, with the total number of samples being 128 students. Data collection techniques in this study are by distributing questionnaires, interviews, and documentation. The questionnaire was made using google forms. Data analysis calculated the percentage of each category indicator and learning motivation aspect, from which the data percentage score was interpreted, and each indicator was analyzed in depth. The results of this study indicate that the learning motivation of students in Yogyakarta in the even semester is in the odd category. This can be seen from the moderate category, as many as 72 students out of 128 students, while from the motivational presentation score with the highest ARSC aspect, the satisfaction aspect is 28%. This research is expected to evaluate various parties involved in organizing online learning in universities so that the implementation is more optimal.